Gerakan Opini Digital pada #TolakUUCiptaKerja di Twitter dengan Pendekatan Social Network Analysis - Rizky Wulan Ramadhani; Fajar Rizali Rakhman; Yohanes Ari Kuncoroyakti; Sabrina Rahma Utami; Cholidah Astri Pertiwi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The ratification of the UU Cipta Kerja led to objections that were echoed through #TolakUUCiptaKerja whose opinions were widely spread on Twitter. The purpose of this study was to determine the digital opinion movement #TolakUUCiptaKerja on Twitter. The research method used was a mix method by combining quantitative communication network statistics with a sample of 1000 tweet data, the number of actors 355 and 344 relations using netlytic and gephi. Qualitative to analyze text with a digital movement of opinion that results in the dissemination of opinions on the structure of the communication network. The results showed that the #TolakUUCiptaKerja movement was able to create mobility in the opinion of Twitter users, namely 752 or 75.2% positive reactions, 7 or 7% negative reactions and 241 or 24.1% irrelevant in communication networks. The positive reaction was dominated by netizen support for rejecting the legalization of the UU Cipta Kerja. The spread of this hashtag was assisted by popular actors, namely @ramlirizal and @ sandalista1789 as important actors, and 205 out of 355 actors were important actors